Biology Teachers: Knowledge in Authentic Assessment Through Cooperative Integrated Reading and Composition Based Scientific Approach (Cirsa) - Rizhal Hendi Ristanto; Refirman Djamahar; Ericka Darmawan (Indonesian Journal of Science and Education (IJOSE), 2020)
Evaluation activities of biology learning process for learners is teachers’ and education units’ responsibility. An authentic assessment is crucial to be implemented in the learning process so that learners could be guided to have abilities in knowledge as well as attitudes and skills. The research aims in 2019 is to observe 50 biology teachers’ differences in biology teachers’ skills in Bekasi Regency, Indoensia in mastering authentic assessment knowledge in biology learning before and after the implementation of training activities through a Scientific Approach-based Cooperative Integrated Reading and Composition (Cirsa).  Cirsa, a learning developed by integrating a CIRC-based scientific approach, axpected to facilitate teacher learning in accordance with the objectives. The research is a quasi-experiment using one group pretest-posttest design. The research independent variable includes Cirsa learning model, whereas the dependent variable is concept understanding of authentic assessment. The research data are analyzed using descriptive statistics that encompasses teachers’ response on learning and analysis of average pretest and posttest. The research results indicate that there is an influence of Cirsa learning application on the concept mastery of authentic assessments of Biology teachers.